2009
DOI: 10.1037/a0016420
|View full text |Cite
|
Sign up to set email alerts
|

Changing, priming, and acting on values: Effects via motivational relations in a circular model.

Abstract: Circular models of values and goals suggest that some motivational aims are consistent with each other, some oppose each other, and others are orthogonal to each other. The present experiments tested this idea explicitly by examining how value confrontation and priming methods influence values and valueconsistent behaviors throughout the entire value system. Experiment 1 revealed that change in 1 set of social values causes motivationally compatible values to increase in importance, whereas motivationally inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
267
3
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(297 citation statements)
references
References 67 publications
17
267
3
10
Order By: Relevance
“…In fact, these dimensions are apparent in patterns of interrelations between the value types across samples from over 70 nations (Schwartz et al, 2012). This prediction has indirectly received support in many studies that have sought evidence that values at opposite ends of the circumplex model exhibit opposing relations to other judgments and behavior (see Maio, Pakizeh, Cheung, & Rees, 2009;Schwartz et al, 2012). This approach is less precise than methods specifically looking at sinusoidal tests of patterns of associations between values and other variables, but one study has recently found evidence of a sinusoidal pattern in relations between values and personality traits (ParksLeduc, Feldman, & Bardi, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…In fact, these dimensions are apparent in patterns of interrelations between the value types across samples from over 70 nations (Schwartz et al, 2012). This prediction has indirectly received support in many studies that have sought evidence that values at opposite ends of the circumplex model exhibit opposing relations to other judgments and behavior (see Maio, Pakizeh, Cheung, & Rees, 2009;Schwartz et al, 2012). This approach is less precise than methods specifically looking at sinusoidal tests of patterns of associations between values and other variables, but one study has recently found evidence of a sinusoidal pattern in relations between values and personality traits (ParksLeduc, Feldman, & Bardi, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…On the one hand, all three subtypes express self-enhancement values of hedonism, power, and achievement, which are antithetical to self-transcendence and social values (Maio et al 2009;Schwartz 1992). This would suggest that their effects on loneliness are comparable.…”
Section: Subtypes Of Materialismmentioning
confidence: 99%
“…Surveys across the world support the theory (Schwartz 1992). Maio et al (2009) tested it in a series of controlled studies. In one study, they increased the importance that participants attached to self-enhancement values and found that this suppressed self-transcendence values, such as being forgiving and honest.…”
Section: Materialism: Crowding Out Social Relationshipsmentioning
confidence: 99%
“…Indeed, basic research relating to what might motivate individuals to save energy in the workplace, and whether specific rewards here may be useful, is currently an open question. Previous research has highlighted a potential conflict between environmental and financial values (Maio et al 2009;Corner, Markowitz, and Pidgeon 2014), indicating that company policy and communications on these issues could undermine each other; however, this remains to be empirically tested in this domain. The social processes that are theorised to operate around the implementation of both individual and collective monitoring and goals, for example, the utility of energy goals and feedback, require field testing in this domain and are likely to interact with the specific institutional context.…”
Section: Discussionmentioning
confidence: 99%